Scientific Opinion on the state of the art of Toxicokinetic/Toxicodynamic (TKTD) effect models for regulatory risk assessment of pesticides for aquatic organisms. (23rd August 2018) - ,; Ockleford, Colin; Adriaanse, Paulien; Berny, Philippe; Brock, Theodorus; Duquesne, Sabine; Grilli, Sandro; Hernandez‐Jerez, Antonio F; Bennekou, Susanne Hougaard; Klein, Michael; Kuhl, Thomas; Laskowski, Ryszard; et al.
Abstract: Following a request from EFSA, the Panel on Plant Protection Products and their Residues (PPR) developed an opinion on the state of the art of Toxicokinetic/Toxicodynamic (TKTD) models and their use in prospective environmental risk assessment (ERA) for pesticides and aquatic organisms. TKTD models are species‐ and compound‐specific and can be used to predict (sub)lethal effects of pesticides under untested (time‐variable) exposure conditions. Three different types of TKTD models are described, viz., (i) the 'General Unified Threshold models of Survival' (GUTS), (ii) those based on the Dynamic Energy Budget theory (DEBtox models), and (iii) models for primary producers. All these TKTD models follow the principle that the processes influencing internal exposure of an organism, (TK), are separated from the processes that lead to damage and effects/mortality (TD). GUTS models can be used to predict survival rate under untested exposure conditions. DEBtox models explore the effects on growth and reproduction of toxicants over time, even over the entire life cycle. TKTD model for primary producers and pesticides have been developed for algae, Lemna and Myriophyllum . For all TKTD model calibration, both toxicity data on standard test species and/or additional species can be used. For validation, substance and species‐specific data sets from independent refined‐exposure experiments are required. Based on the current state of the art (e.g. lack of documented and evaluated examples), the DEBtox modelling approach is currently limited to research applications. However, its great potential for future use in prospective ERA for pesticides is recognised. The GUTS model and the Lemna model are considered ready to be used in risk assessment.